Ionizing radiation exposure in patients with inflammatory bowel disease: Are we overexposing our patients?. Issue 2 (February 2015) - Estay, Camila; Simian, Daniela; Lubascher, Jaime; Figueroa, Carolina; O'Brien, Andrés; Quera, Rodrigo
<x xml:space="preserve">Abstract</x> Objective Imaging techniques are accurate and reliable in diagnosing inflammatory bowel disease (IBD). However, the main disadvantage of computed tomography (CT) compared with magnetic resonance imaging (MRI) is radiation exposure and the potential risk of cancer, especially since IBD patients are at increased risk of malignancies. This study aims to quantify and characterize effective radiation exposure of IBD patients. Methods A cohort of IBD patients were retrospectively enrolled in the Clínica las Condes IBD registry between 2011 and 2013. High cumulative radiation exposure (CED) was defined as ≥−50 mSv. Results A total of 325 IBD patients were enrolled in our registry, including 243 (74.8%) with UC and 82 (25.2%) with CD. The patients with CD were more commonly to reach a high CED seen compared with those with UC (19.5% vs 2.5%). Higher exposure to radiation was associated with longer duration of disease, ileal involvement, stricturing behavior, treatments with steroids and biological agents and CD‐related hospitalization or surgery. Abdominopelvic CT and enteroclysis CT accounted for 93.6% of total CED. Conclusions A high percentage of IBD patients are exposed to high CED. Radiation‐free cross‐sectional examinations, such as MRI, should be used, especially in young patients, those who have undergone prior surgery and those with severe IBD.